2017
DOI: 10.47672/ijbs.283
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Risk Identification on Performance of Financial Institutions

Abstract: Purpose: The purpose of the study was to determine the effect of risk identification on performance of financial institutions.Methodology: The study used explanatory research design. The study used stratified random sampling to select respondents from target population comprising of managers of 46 commercial banks, 52 Micro Finance institutions (MFIs) and 200 SACCOs and a sample size of 239 respondents obtained. Data was collected using questionnaires. Descriptive statistics was presented, while inferential st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…The findings indicated that all the respondents agreed that financial risk identification affected financial performance of small and medium enterprises in Hirshabelle state-Somalia with an aggregate mean of 3.41. The study concurs with findings by (Lagat & Tenai, 2017), that risk identification ensures risk management effectiveness and that when managers do not succeed in identifying all possible losses or gains that challenge the organization, then these nonidentified risks will become non-manageable. Risk identification reveals and determines the potential risks which are highly occurring and other events which occur very frequently.…”
Section: Methodssupporting
confidence: 87%
See 1 more Smart Citation
“…The findings indicated that all the respondents agreed that financial risk identification affected financial performance of small and medium enterprises in Hirshabelle state-Somalia with an aggregate mean of 3.41. The study concurs with findings by (Lagat & Tenai, 2017), that risk identification ensures risk management effectiveness and that when managers do not succeed in identifying all possible losses or gains that challenge the organization, then these nonidentified risks will become non-manageable. Risk identification reveals and determines the potential risks which are highly occurring and other events which occur very frequently.…”
Section: Methodssupporting
confidence: 87%
“…Risk identification ensures risk management effectiveness and that when managers do not succeed in identifying all possible losses or gains that challenge the organization, then these nonidentified risks will become non-manageable. (Lagat & Tenai, 2017) Risk identification process needs to be a continuing process, and should be understood at both the transaction and portfolio levels. Risk identification reveals and determines the potential risks which are highly occurring and other events which occur very frequently.…”
Section: Financial Risk Identificationmentioning
confidence: 99%
“…The results of this study are consistent with theory of risk return, namely there is direct relationship between risk and return. That theory is known as efficient market theory, also in line with Lagat F. Kiprop [42] and Thitima Chaiyakul [27], who found a positive relationship between risk and financial performance but on contrary with Yu -Luen Ma & Yayuan Ren [30] which found a negative relationship between institutional ownership measured by (ratio of equity owned) and financial performance of insures during the financial crisis of 2008, but the relationship between institutional ownership with risk is positive, and the results consistent with asymmetric information approach Greenwald, Bruce and Stiglitz, Joseph E (43).…”
Section: Parameter Estimatesmentioning
confidence: 89%
“…It establishes the foundation for subsequent procedures, such as risk analysis and risk control, and assures the success of risk management (Hopkin, 2018). If risk managers fail to identify all potential losses or profits that pose a threat to the firm, these unidentified risks will become unmanageable (Lagat & Tenai, 2017). The organization will not account for them and will not take any activities in their behalf, and the results may be unexpected (Salichos, 2015).…”
Section: Risk Identificationmentioning
confidence: 99%